INCREASE PRODUCTIVITY EMPLOYEE THROUGH LEADERSHIP AND WORK ENVIRONMENT: THE ROLE OF WORK MOTIVATION AS A INTERVENING VARIABLES AT PT. AMS YAMAHA FORTUNA CIPARAY - Iis Nurjanah; Widiya Avianti (Journal of Economic Empowerment Strategy (JEES), 2026)
This study aimed to determine and analyze the level of work discipline, work motivation, and employee performance at the West Bandung Regency Youth and Sports Office, as well as to examine the influence of work discipline and work motivation on employee performance within the institution. The research employed a quantitative approach with descriptive verification methods, which allowed the researcher to describe existing conditions and then verify the relationship between variables through statistical testing. The population in this study consisted of all employees at the West Bandung Regency Youth and Sports Office, with saturated sampling used to ensure that every member of the population was included as a respondent. Data were collected using a structured questionnaire, while multiple linear regression analysis and the coefficient of determination were applied with the support of SPSS 26 to measure the extent of influence between the variables studied. The findings showed that the levels of work discipline, work motivation, and employee performance at the West Bandung Regency Youth and Sports Office were generally categorized as high. Employees demonstrate adherence to organizational rules, commitment to punctuality, and respect for established procedures, all of which reflect strong work discipline. Likewise, employee work motivation was found to be high, supported by teamwork, interpersonal relationships, and a conducive work environment that encourages productivity. Employee performance also showed positive results, reflected in the ability to work collaboratively, fulfill responsibilities, and contribute actively to organizational tasks. Based on statistical tests, it can be concluded that work discipline and work motivation have a very strong and significant influence on employee performance. The coefficient of determination indicated that 88.5% of employee performance is influenced by work discipline and work motivation, while the remaining 11.5% is explained by other variables not examined in this study. These results emphasize the importance of enforcing discipline and enhancing motivation to improve overall organizational performance.